Ellagic acid attenuates arsenic induced neuro-inflammation and mitochondrial dysfunction associated apoptosis. (2018) - Firdaus, Fakiha; Zafeer, Mohd Faraz; Anis, Ehraz; Ahmad, Masood; Afzal, Mohammad
Graphical abstract: Highlights: Ellagic acid mitigates arsenic mediated genotoxicity in rat brain hippocampi. Ellagic acid ameliorates arsenic induced exacerbation in levels of ROS and pro-inflammatory cytokines in rat brain hippocampi. Ellagic acid has the propensity to modulate mRNA expression of BAX, Bcl2 and caspase3, suggestive of its neuroprotective efficacy. Abstract: Arsenic, being a global pollutant needs a potential remedy which could fight against its associated toxicities. Ellagic acid (EA) is a known agent for its anti-inflammatory, antioxidant and antiapoptotic effects, and it is commonly found in fruits. The present study is designed to determine protective efficacy of EA against arsenic induced toxicity with special mention to inflammation and mitochondrial dysfunction in hippocampi of wistar rats. Rats were pre-treated with EA (20 and 40 mg/kg b.wt; p.o. for 11 days) along with arsenic (10 mg/kg; p.o. for 8 days). Total reactive oxygen species level and mitochondrial membrane potential were analyzed using flow cytometry. Protein and mRNA expression of apoptotic and inflammatory markers were also evaluated in rat hippocampus. Our results show that arsenic exposure increased total ROS generation and DNA fragmentation, decreased mitochondrial membrane potential alongwith an increase in expression of pro-apoptotic and inflammatory markers. suggesting that EA complementation downregulated total ROS generation dose dependently. Apoptotic markers, BAX and Bcl2 as well as inflammatory markers, IL-1β, TNFα, INFγ got altered significantly on its administration. Moreover, it also attenuated effects on mitochondrial membrane potential. Based on our findings, EA might substantiate to be a budding therapeutic candidate against arsenic induced neurotoxicity.